GANGGUAN BERBAHASA PSIKOGENIK LATAH PADA GRUP CAP TAWA DALAM ACARA BROWNIS TRANS TV: TINJAUAN PSIKOLINGUISTIK - Hermawan, Dimas; Ginanjar, Agi Ahmad (Universitas Tanjungpura, 2025)
Cap Tawa is a comedy group consisting of three talkative middle-aged man, namely Deddy, Bayu, and Gary Iskak. In the realm of psycholinguistics, talkative is classified as one of the psychogenic language disorders. This research purposed to investigate the psychogenic language disorder of talkative in the Cap Tawa group on the Brownis Trans TV